2018
DOI: 10.1186/s12916-018-1173-9
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with chemically attenuated Plasmodium falciparum asexual blood-stage parasites induces parasite-specific cellular immune responses in malaria-naïve volunteers: a pilot study

Abstract: BackgroundThe continuing morbidity and mortality associated with infection with malaria parasites highlights the urgent need for a vaccine. The efficacy of sub-unit vaccines tested in clinical trials in malaria-endemic areas has thus far been disappointing, sparking renewed interest in the whole parasite vaccine approach. We previously showed that a chemically attenuated whole parasite asexual blood-stage vaccine induced CD4+ T cell-dependent protection against challenge with homologous and heterologous parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 45 publications
0
39
0
1
Order By: Relevance
“…There are few reports of species-transcending T-cells in humans. The most definitive study showed that T-cells isolated from volunteers immunized with attenuated blood stage P. falciparum parasites proliferated in vitro in response to P. knowlesi iRBCs (54). Whether these T-cells have functional activity to protect against heterologous challenge is not known.…”
Section: Cross-reactive T-cellsmentioning
confidence: 99%
“…There are few reports of species-transcending T-cells in humans. The most definitive study showed that T-cells isolated from volunteers immunized with attenuated blood stage P. falciparum parasites proliferated in vitro in response to P. knowlesi iRBCs (54). Whether these T-cells have functional activity to protect against heterologous challenge is not known.…”
Section: Cross-reactive T-cellsmentioning
confidence: 99%
“…Several reports of Good' team showed that cellular immune responses and protection were induced by different chemically attenuated parasites in various murine models [16,23] and in humans [6,26]. Actually, a long-lasting cellular immune response was observed in a small number of human volunteers induced by chemically attenuated P. falciparum followed by a drug treatment [7]. However, no parasite challenge was analysed thereafter and need further work to establish if this reactive immune response will be cross protective in humans.…”
Section: Plos Onementioning
confidence: 99%
“…As for the living red blood cell (RBC) vaccines, the first report [6] showed that a low amount as low as 30-300 P. falciparum parasitized RBC (iRBC) infected with the 3D7 Plasmodium live parasites when injected four times to five volunteers followed by an anti-malarial treatment triggered a some protection against an homologous challenge. Thereafter, several trials were achieved with living parasites followed by antimalarial treatment [7,8] as well as with chemically attenuated P. falciparum [7]. In addition, several genetically attenuated parasites with defects in replication capacity have been shown to lead to self-resolving infections leading possibly to potent and long-lasting protection in various murine models against both erythrocytic [9,10,11] and pre-erythrocytic [4,12,13,14] challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stanisic et al [ 14 ] present a pilot study evaluating the safety and immunogenicity of a chemically attenuated Plasmodium falciparum asexual blood-stage vaccine in malaria-naïve human subjects. This is the first clinical study of its kind.…”
Section: Addressing the Challenges For Developmentmentioning
confidence: 99%